2020
DOI: 10.1111/cpr.12865
|View full text |Cite
|
Sign up to set email alerts
|

Modifying the tumour microenvironment and reverting tumour cells: New strategies for treating malignant tumours

Abstract: The tumour microenvironment (TME) plays a pivotal role in tumour fate determination. The TME acts together with the genetic material of tumour cells to determine their initiation, metastasis and drug resistance. Stromal cells in the TME promote the growth and metastasis of tumour cells by secreting soluble molecules or exosomes. The abnormal microenvironment reduces immune surveillance and tumour killing. The TME causes low anti‐tumour drug penetration and reactivity and high drug resistance. Tumour angiogenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(44 citation statements)
references
References 183 publications
(365 reference statements)
0
44
0
Order By: Relevance
“… 208 Inhibition of the TGFβ signaling pathway in CAFs has been found to result in reduced collagen I secretion, resulting in reduced extracellular matrix stiffness. 209 Previous studies have shown that tumor resistance to ICP-targeting therapy was associated with a TGFβ signaling signature in fibroblasts. 208 , 210 Combining TGFβ-blockade with anti-PD-L1 antibodies has reduced TGFβ signaling in stromal cells, facilitated T-cell infiltration, and provoked vigorous antitumor immunity and tumor regression in a mouse model.…”
Section: Combined Time-targeted Therapy and Icp Inhibitor Treatmentmentioning
confidence: 99%
“… 208 Inhibition of the TGFβ signaling pathway in CAFs has been found to result in reduced collagen I secretion, resulting in reduced extracellular matrix stiffness. 209 Previous studies have shown that tumor resistance to ICP-targeting therapy was associated with a TGFβ signaling signature in fibroblasts. 208 , 210 Combining TGFβ-blockade with anti-PD-L1 antibodies has reduced TGFβ signaling in stromal cells, facilitated T-cell infiltration, and provoked vigorous antitumor immunity and tumor regression in a mouse model.…”
Section: Combined Time-targeted Therapy and Icp Inhibitor Treatmentmentioning
confidence: 99%
“…These tumor-associated cells secrete soluble molecules and microvesicles that control the interactions of cancer cells with other cell types. This can influence how the tumor cells proliferate, oppose apoptosis, avoid elimination from the immune system, preserve stemness, invade, and metastasize ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although the acquisition of genetic mutations can drive therapeutic drug resistance mechanisms, another route by which resistance can emerge is through cell-cell communication within the heterogeneous tumour and with its stroma (Cheng et al, 2020). One evolutionarily conserved mechanism of intercellular signalling involves the transfer of extracellular vesicles (EVs) between cells (Meldolesi, 2018).…”
Section: Introductionmentioning
confidence: 99%